The treatment of severe malaria. - Dondorp, A; Day, N (2007)
In the SEAQUAMAT trial, parenteral artesunate was shown to be associated with a considerably lower mortality than quinine, and is now the recommended treatment for severe malaria in low-transmission areas and in the second and third trimesters of pregnancy. A trial is underway to establish its role in African children. The development of artesunate suppositories may provide the means to treat patients with severe disease in remote rural settings, potentially buying the time needed to reach a health care facility. The increasing availability of basic intensive care facilities in developing countries also has the potential to further reduce mortality.